The Effectiveness of Succession in a Family Business: Case Study on Batik Industry in Indonesia - Istiatin Istiatin; Ari Susanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study is; To describe succession planning and an effective succession model, to create a successful successor, to describe the planning and design an effective succession model, and to create a successful successor in both PT. Danliris and Batik Semar. The method used in this study is qualitative descriptive. Data collection is by observation and using in-depth interviews. Informant selection was determined by purposive sampling. The validity of the data was tested by the source triangulation. The results show that PT. Danliris has been succesfully done the succession because the founder involved the successor. Although the delivery of the succession was unplanned, the mentoring process went naturally and create the third generation as the successor who has good responsibility for the sustainability of the family business. In the other hand, PT. Batik Semar did not perform succession effectively because the founder did not involve the successor. The founder still in charge in family business’ operations. The third Generation of Batik Semar is currently still leading and the successor just become passive leader. And up to now, the decision makers are still done by the founder. Keywords; Family Business, succession planning, effective succession model, qualified successor.